2018
DOI: 10.3847/1538-4357/aabcb9
|View full text |Cite
|
Sign up to set email alerts
|

The Diffuse Radiation Field at High Galactic Latitudes

Abstract: We have used GALEX observations of the North and South Galactic poles to study the diffuse ultraviolet background at locations where the Galactic light is expected to be at a minimum. We find offsets of 230 -290 photon units in the FUV (1531 Å) and 480 -580 photon units in the NUV (2361 Å). Of this, approximately 120 photon units can be ascribed to dust scattered light and another 110 (190 in the NUV) photon units to extragalactic radiation. The remaining radiation is, as yet, unidentified and amounts to 120 -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 61 publications
7
44
0
Order By: Relevance
“…We have studied the latitude range between 70 • and 80 • as a continuation of our characterisation of the diffuse UV sky. This region has a greater amount of nebulosity and hence higher column densities than our earlier study at the Galactic Poles (Akshaya et al 2018). We confirm the presence of an offset at zero column density (E(B -V) = 0) with a level of 240 ± 18 photon units in the FUV and 394 ± 37 photon units in the NUV, slightly higher than in the polar regions (Akshaya et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…We have studied the latitude range between 70 • and 80 • as a continuation of our characterisation of the diffuse UV sky. This region has a greater amount of nebulosity and hence higher column densities than our earlier study at the Galactic Poles (Akshaya et al 2018). We confirm the presence of an offset at zero column density (E(B -V) = 0) with a level of 240 ± 18 photon units in the FUV and 394 ± 37 photon units in the NUV, slightly higher than in the polar regions (Akshaya et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Their final diffuse radiation maps in FUV and NUV are dominated by starlight scattered by Milky Way dust, especially at low latitudes. At high latitudes, the extragalactic contribution is significant but its amplitude is under debate, due to the uncertainties in the near-Earth and Galactic foregrounds (Hamden et al 2013;Henry et al 2015;Akshaya et al 2018). Our cross-correlation analysis has the advantage that the result should not be biased by the presence of foregrounds, as they only add noise but do not correlate with extragalactic large-scale structures.…”
Section: Diffuse Lightmentioning
confidence: 99%
“…The all-sky nature of the GALEX and the SPEAR observations have allowed us to separate the components based on their distribution over the sky. The foreground emission (airglow and zodiacal light) is dependent on the observation time and date and Murthy (2014b) has characterized their contribution to the total diffuse background in the GALEX data while Akshaya et al (2018Akshaya et al ( , 2019 have mapped the contributions from the Galactic and extragalactic components at high latitudes. Similarly, Seon et al (2011) andJo et al (2017) have mapped the diffuse emission observed by SPEAR, both the continuum dust emission and the molecular hydrogen fluorescence with the advantage over GALEX of spectroscopy but a poorer sensitivity and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the contributors to the diffuse observations, the only one which might be expected to be time-variable is the airglow, which is a function of the local time of observation (Murthy 2014b), and it was a surprise when Akshaya et al (2018) found time-variable variations in the GALEX observations in Virgo, which they attributed to unknown atmospheric sources. GALEX was never intended to probe variability in the DGL and it is difficult now, after the mission has ended, to divine the source of the variability.…”
Section: Introductionmentioning
confidence: 99%